Mediacja jako szansa pojednania sprawcy i ofiary przestępstwa w sprawach z zakresu prawa karnego - Matysiak-Błaszczyk, Agata; Rajewska de Mezer, Joanna (Wydawnictwo Naukowe UAM, 2016)
Mediation is a result of searching for new, rational alternative means of responding to crime and methods to include a wider range of the victims’ interests. The aim of mediation is the settlement and reconciliation between the victim and the offender. It is based on negotiations between the mediator, an impartial observer. Parties involved in the mediation process should be able to openly and honestly express their views and feelings and to proceed a voluntary, negotiated conflict-free way to redress the damage caused by the offender in the presence of a mediator.
Mediation as a Chance for the Reconciliation of the Perpetrator and Victim of a Criminal Offence
Keywords: mediation; mediator; crime; criminal law; satisfaction